Sustaining innovation : collaboration models for a complex world - Carleton, Tamara; MacGregor, Steven P. (Innovation, Technology, and Knowledge Management, 2012)
In many ways, the process of innovation is a constant social dance, where the best dancers thrive by adapting new steps with multiple partners. The systematic and continuous generation of value in any innovation system relies on collaboration between different groups, who must overcome multiple, often competing agendas and needs to work together fruitfully over the long term. Featuring contributions from leading researchers, business leaders, and policymakers representing North America, Europe, India, Africa, and Australasia, this volume investigates different combinations of collaborative arrangements among innovation actors, many of which are changing conventional expectations of institutional relationships. Collectively, the authors demonstrate that no particular combination has emerged as the most dominant, or even resilient, model of innovation. Several authors expand on our understanding of the triple helix model, with both academics and practitioners looking to the quadruple helix (encompassing business, academic, government, and civil society) as the new standard. Other authors address aspects of open innovation, co-creation, and user-centered design-all testaments to the rapidly shifting landscape. At the same time, many businesses, academics, and governments, not to mention non-profit organizations, foundations, and society at large, are active in conversations about how to pursue a more sustainable model of innovation. The pursuit of this holy grail of innovation is both facilitated and complicated by an ever-accelerating technological environment in which social networking and mobile tools are emerging as new dance arenas.